การพัฒนาบทเรียนภาษาอังกฤษที่เน้นเนื้อหาพระพุทธศาสนา ตามแนวการสอนภาษาเพื่อการสื่อสาร - อภัยโส, พลภัทร; โชติชัย, บรรจบ; ทาวงศ์ษา, กิตติพัฒน์; สาริยา, วันชัย; ศรีโนนยาง, ประดิษฐ์ (วารสารศรีล้านช้างปริทรรศน์, 2017)
งานวิจัยฉบับนี้มีวัตถุประสงค์ 1) เพื่อพัฒนาบทเรียนภาษาอังกฤษที่เน้นเนื้อหาพระพุทธศาสนาตามแนวการสอนภาษาเพื่อการสื่อสาร 2) เพื่อศึกษาความสามารถในการสื่อสารภาษาอังกฤษของนักศึกษาจากการเรียนบทเรียนภาษาอังกฤษที่เน้นเนื้อหาพระพุทธศาสนาตามแนวการสอนภาษาเพื่อการสื่อสาร และ 3) เพื่อศึกษาความคิดเห็นของนักศึกษาที่มีต่อบทเรียนภาษา อังกฤษที่เน้นเนื้อหาพระพุทธศาสนาตามแนวการสอนภาษาเพื่อการสื่อสารหลังการเรียนการสอน  กลุ่มเป้าหมายเป็นนักศึกษาชั้นศึกษาศาสตรบัณฑิตปีที่ 1 ที่กำลังศึกษารายวิชา ภาษาอังกฤษเพื่อการสื่อสารและการสืบค้น (English for Communication and Information Retrieval) รหัสวิชา GE3003 จำนวน 18 คน เครื่องมือที่ใช้สำหรับเก็บรวบรวมข้อมูลเป็นแบบวัดความสามารถในการพูดภาษาอังกฤษ ซึ่งออกแบบตามเกณฑ์การประเมินผลความสามารถในการพูดของ D. P. Harris และแบบวัดความคิดเห็นของนักศึกษาต่อบทเรียนภาษาอังกฤษที่เน้นเนื้อหาพระพุทธ-ศาสนาตามแนวการสอนภาษาเพื่อการสื่อสาร สถิติที่ใช้ในการวิจัยประกอบด้วยค่าเฉลี่ย ค่าร้อยละ และส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า 1. บทเรียนภาษาอังกฤษที่เน้นเนื้อหาพระพุทธศาสนาตามแนวการสอนภาษาเพื่อการสื่อสารที่พัฒนาขึ้นจากความต้องการของนักศึกษาประกอบ ด้วยเนื้อหาจำนวน 6 บท ประกอบด้วย Unit 1: Buddhism in Thailand, Unit 2: Wat Srisuddhavasa (Royal Temple), Unit 3: Buddhist Monk Ordination, Unit 4: Buddhist Sacred Days, Unit 5: Ovadapatimokkha, and Unit 6: Significant Principles of Buddhism. สามารถนำมาใช้ประกอบการเรียนการสอนในรายวิชา ภาษาอังกฤษเพื่อการสื่อสารและการสืบค้นได้ 2. ความสามารถในการสื่อสารภาษาอังกฤษของนักศึกษา หลังการเรียนบทเรียนภาษาอังกฤษที่เน้นเนื้อหาพระพุทธศาสนาตามแนวการสอนภาษาเพื่อการสื่อสาร พบว่า มีระดับ ความสามารถเพิ่มขึ้นโดยลำดับ โดยเฉพาะในขั้นปฏิบัติซึ่งนักศึกษาได้เลือกจับคู่และกำหนดบทบาทสมมติ (role-playing) ด้วยตนเอง 3. ระดับความคิดเห็นต่อบทเรียนภาษาอังกฤษที่เน้นเนื้อหาพระพุทธศาสนาตามแนวการสอน ภาษาเพื่อการสื่อสารทั้งโดยรวมและรายด้านอยู่ในระดับมากทุกด้าน โดยด้านวิชาการ มีค่าเฉลี่ยอยู่ที่ 3.98 ด้านสังคม 3.84 และด้านอารมณ์และความรู้สึก 3.78 4. ข้อเสนอแนะจากการวิจัยในครั้งนี้พบว่า ควรมีการวัดความสามารถด้านการฟัง การ อ่านและการเขียนเพิ่มขึ้น ควรจัดให้มีการแข่งขันทักษะทางวิชาการเกี่ยวกับคำศัพท์ทางพระพุทธ-ศาสนาในชั้นเรียน และควรมีการบูรณาการความรู้ด้านพระพุทธศาสนาเข้ากับรายวิชาภาษา อังกฤษทุกรายวิชา           The objectives of the research were 1) to develop the Buddhist contentbased English lessons through the communicative language teaching (CLT), 2) to study the student’s English communication competence after learning the Buddhist content-based English lessons through the communicative language teaching (CLT), and 3) to study the student’s opinions toward the Buddhist content-based English lessons through the communicative language teaching (CLT). The target group of the research were 18 first-year students studying the subject ‘English for Communication and Information Retrieval (GE3003)’. The instruments of the research were the observation form based on D.P. Harris’ English speaking competence assessment and Likert’s five-point rating scale questionnaire on the student’s opinions toward the Buddhist content-based English lessons through the communicative language teaching (CLT). The statistics used for data analysis were comprised of mean, percentage and standard deviation. The research findings were as follows: 1. The Buddhist content-based English lessons through the communicative language teaching (CLT), comprised of six lessons: Unit 1: Buddhism in Thailand, Unit 2: Wat Srisuddhavasa (Royal Temple), Unit 3: Buddhist Monk Ordination, Unit 4: Buddhist Sacred Days, Unit 5: Ovadapatimokkha, and Unit 6: Significant Principles of Buddhism, were found to be used in lecturing the subject ‘English for Communication and Information Retrieval (GE3003)’. 2. After learning the Buddhist content-based English lessons through the communicative language teaching (CLT), the student’s English communicative competence was found increased simultaneously, especially in the practical level which a pair of students themselves decided to select their own partners and create their own role-playing activities. 3. The student’s opinions toward the Buddhist content-based English lessons through the communicative language teaching (CLT) were found to be overall and in each aspect at a high level. Considered in each aspect, the academic aspect was ง found to be at a high level of mean (= 3.98), the social aspect (= 3.84), and the emotion and feeling (= 3.78). 4. The recommendations of the research were found that the competence of listening, reading and writing skills should be assessed, the competition of academic skills on Buddhist vocabularies in English classes, and Buddhism should be integrated into all English subjects.